Clinical significance of the expression of autophagy-associated marker, beclin 1, in breast cancer patients who received neoadjuvant endocrine therapy. Issue 1 (December 2016) - Ueno, Takayuki; Saji, Shigehira; Sugimoto, Masahiro; Masuda, Norikazu; Kuroi, Katsumasa; Sato, Nobuaki; Takei, Hiroyuki; Yamamoto, Yutaka; Ohno, Shinji; Yamashita, Hiroko; Hisamatsu, Kazufumi; Aogi, Kenjiro; et al.
Abstract Background Neoadjuvant endocrine therapy (NAE) has been employed to improve surgical outcomes for hormone receptor-positive breast cancers in postmenopausal women. Endocrine responsiveness is estimated by expressions of hormone receptors, but its heterogeneity has been recognized. Autophagy is an evolutionally conserved process associated with cell survival and cell death and has been implicated in cancer treatment. Methods In order to examine the possible association between autophagy and response to endocrine therapy, we evaluated the status of autophagy-associated markers, beclin 1 and LC3, and apoptosis-associated markers, TUNEL and M30, in pre- and post-treatment specimens from 71 patients in a multicenter prospective study of neoadjuvant exemestane (JFMC34-0601). Results Immunoreactivity of the autophagy-associated markers, beclin 1 and LC3, in carcinoma cells increased in 14 % and 52 % of the patients, respectively, following the exemestane treatment. These increases were statistically significant (beclin 1, p = 0.016, N = 49; LC3, p < 0.0001, N = 33). The status of M30 immunoreactivity decreased (p = 0.008, N = 47) and TUNEL remained unchanged (N = 53). In addition, tumors with pre-treatment stromal beclin 1 immunoreactivity revealed poor clinical and pathological responses compared with those without stromal beclin 1 immunoreactivity (25 % vs 67 % for clinical response, p = 0.011, N = 51; 0 % vs 41 % for pathological response, p = 0.0081, N = 49). Tumors with positive pre-treatment stromal beclin 1 had a higher baseline Ki-67 labeling index (both hot spot and overall average) than those without (p = 0.042 and 0.0075, respectively, N = 53). Results of logistic regression analyses revealed that stromal beclin 1 was a predictor for clinical and pathological responses while ER, PR, Ki-67, and stromal LC3 expressions were not. Conclusions Results of our present study demonstrated that beclin 1 and LC3 immunoreactivity increased in carcinoma cells following exemestane treatment and that the status of pre-treatment stromal beclin 1 is associated with higher carcinoma cell proliferation and poor clinical and pathological responses to NAE. Trial registration UMINC000000345 (2006/03/06)